THE RECENT DEVELOPMENT OF AGARWOOD PRODUCT INVENTION IN INDONESIA - Triandini, I Gusti Agung Ayu Hari; Wangiyana, I Gde Adi Suryawan (Universitas Pendidikan Mandalika, 2025)
The invention of agarwood is crucial for the downstream application of agarwood research results in Indonesia. This study aims to review the invention of agarwood in Indonesia over the past 8 years. According to the Indonesian Intellectual Property Database, the average number of agarwood inventions in Indonesia from 2018 to 2025 is approximately five inventions per year. This number is much lower than the average number of agarwood publications during the same period, which can reach 81 publications per year. Agarwood leaf utilisation accounts for the dominant proportion of the invention, which is equally derived from the Aquilaria and Gyrinops genera. Most of the invention is intended to produce health products that confirm the health-beneficial effects of agarwood, based on research. The invention of agarwood in Indonesia was dominated by simple patents, which are easier to register compared to other types of patents. The proportion of rejected inventions to granted inventions is 1:6, indicating a medium difficulty level of invention registration in Indonesia. The invention right holder is dominated by higher education institutions (70%), followed by research institutions with a proportion of less than 20%. Invention registration location data reveal the uneven distribution of agarwood inventions, which is dominated by three islands: Java, Sumatra, and Kalimantan. It can be concluded that the invention of agarwood in Indonesia is very limited compared to the number of publications, with a minimal contribution from the Industrial sector.